IoT -Based Electrical Distribution Box Power Monitoring System Using Raspberry PI - Amir Hamzah, AMIRUL; abu hassan, omar (Progress in Engineering Application and Technology, 2024)
The Projecy is a sophisticated solution designed to empower homeowners with the ability to monitor and manage power consumption at the circuit level within their residential electrical distribution box. The system is built around the Raspberry Pi 3 Model B and utilizes two key sensors: the ZMPT101B for voltage measurement and the SCT-013 for current measurement. This project addresses the pressing need for homeowners to optimize energy efficiency, enhance electrical safety, and reduce utility expenses. The core functionalities of this system include real-time power monitoring, data logging, abnormality detection, and instant notifications to homeowners in case of power anomalies, such as surges, overloads, or short circuits. The intuitive web interface and mobile application grant users’ remote access to the system, allowing them to visualize real-time power data, control individual circuits, and receive timely notifications. The integrated user authentication ensures security and control. The ZMPT101B and SCT-013 sensors are accurately interfaced with the Raspberry Pi 3, and their output is processed to provide precise measurements of voltage and current on individual circuits. The system takes advantage of the Raspberry Pi's processing power and GPIO capabilities to create a robust solution that is both reliable and efficient. In summary, this project offers homeowners a comprehensive solution to enhance energy efficiency, electrical safety, and cost management. Through meticulous sensor integration, data analysis, and user-friendly interfaces, this project aims to transform the way homeowners interact with and monitor their electrical systems